Analisis Kesalahan Siswa dalam Menyelesaikan Soal Matematika HOTS Bertipe PISA - Sa'adah, Amiratus; Misri, Muhamad Ali; -, Darwan (Holistik: Journal for Islamic Social Sciences, 2019)
The purpose of this study is to describe the types of errors and the factors causing the occurrence of student errors in completing PISA HOTS questions in SMP Negeri 1 Sumber based on the Newman’s Error Analysis (NEA) category. This type of research is a descriptive qualitative research. Data collection techniques using test and interview methods, involving 35 students to carry out the test and taken 5 students for interviews. The validity of the data is done by triangulation by comparing data from test and interview methods. Data analysis techniques using data reduction, data presentation and data verification then drawing conclusions. The analysis framework was developed based on the error categories of Newman's Error Analysis (NEA) consisting of 5 errors obtained by the results of the study, namely errors made by students there are 4 types of errors based on the classification of Newman's Error Analysis (NEA) with the following percentage: error understanding 29.74%, errors transform 27.51%, error in process capability 26.39% and error writing final answer 16.36%. In general the factors causing errors are the low ability of reasoning and creativity of students in solving mathematical problems, the ability of students who are weak in manipulating data in the form of images and tables into mathematical models and students are not careful in writing the final results. This research is expected to be able to increase knowledge about the types of errors made by junior high school students in working on MATS Mathematics HOTS types of PISA so that the mistakes made can be minimized.